Simulation of propranolol as antihypertensive agent on hyperglicaemic rabbit - Kus Haryono; Sukati K.; Elly Wahyuddin (Indonesian Journal of Pharmacy, 2006)
Diabetic and hypertention are two common deseases on older people one of fat soluble antihypertensive drugs is propanolol. There for is a study this undertakento observe how propanolol can reduce the blood sugar. This study used 12 male rabbits, divided into 4 grroups. Each group consisted 3 rabbits. The first group was used as negative control (given EDTA sodium liquid 1 % w/v). The second group was the treated group (given EDTA sodium suspension 1.% w/v and propranolol tablet suspension 0,006.% w/v). The third group also the treated group (given EDTA sodium suspension 1% and propranolol tablet suspension 0,02 % w/v). The fourth group was the positive control (given EDTA sodium liquid 1 % w/v only). Blood glucose level was measured before and after treatment by using spektrophotometer (578 nm). The result showed that colloidal CMC sodium liquid 1 % w/v lowered blood glucose level (not significant as 0,7 mg/dL). EDTA sodium liquid 1 % w/v + propranolol suspension 0,006 % w/v significantly lowered blood glucose level as 5,3 mg/dL, EDTA sodium liquid 1 % w/v + propranolol suspension 0,02% w/v also lowered the blood glucose level as 21,7 mg/dL, EDTA sodium liquid 1 % w/v significantly giving the effect on the increasing blood glucose level as 17,4 mg/dL.Key words : Propranolol, glucose, rabbit